Hijacked pathways: PFOS, the ATF2/WT1 axis, and the mitochondrial dysfunction in Sertoli cells - Jinchen Jiang; Haixia Meng; Hongxia Wang; Shaokai Zheng; Lianlian Jiang; Nannan Zhao; Xiaojun Lin; Jianglan Li; Minjun Qin; Siyu Wu; Lianglin Qiu (Toxicology Letters, 2026)

ABA-dependent priming of stomatal immunity by the harpin protein PopW restricts entry of Xanthomonas euvesicatoria in tomato - Xiaosi Zhou; Tian Wei; Yuwei Xue; Jiangfei Hu; Yuqing Lin; Lina Xu; Hongwei Zhao; Hongxia Liu (Plant Science, 2026)

Three-dimensional reconstruction reveals distinct endodermal network topology associated with root ion transport characteristics in balsa - Taining Pei; Jinyuan Xiong; Hongxia Lin; Yuqian Zhang; Jiangming Wang; Qian Niu; Xi Zhang; Xiaojuan Li; Yuanyuan Zhao (Journal of Plant Physiology, 2026)

Residual dissipation, processing factor and risk assessment of three pesticides in peaches from field to juice processing - Zehui Liu; Yujiao Wang; Dianying Men; Lin Ma; Guangyue Wen; Shaoxiang Fei; Hongxia Tang; Yanna Han; Maofeng Dong; Li Zhao (Food Control, 2026)

Sustainable mechanochromism and photochromism achieved by incorporating rhodamine into dialdehyde bacterial cellulose - Zheyu Shen; Qiuhao Yi; Bianjing Sun; Yalei Qiao; Xinyu Chen; Chenchen Qin; Lin Shi; Hongxia Qu; Chuntao Chen; Dongping Sun (Chemical Engineering Journal, 2026)

Acid-catalyzed ethanol pretreatment of sugarcane bagasse enables electrochemically improved hard carbon anodes for sodium-ion batteries - Nethmi Kulanika Dayarathne; Eric Campbell; Mu Xiao; Jiaye Ye; Cheng Yan; Hongxia Wang; Dawei Wang; Yu Lin Zhong; Zhanying Zhang (Chemical Engineering Journal, 2026)

Ternary synergistic activation of municipal waste incineration bottom ash for high-performance supplementary cementitious materials: Mechanisms, heavy metal immobilization, and sustainability - Jianwen Xiao; Hongxia Qiao; Minggang Shang; Lexiang Nie; Wenhao He; Feng Cao; Gangliang Lin (Environmental Research, 2026)

Fecal pollution source tracking at a marine bathing beach: A case study of Beihai Silver Beach - Hongxia Ming; Ziqi Chen; Tingting Shi; Zhongzhi Chen; Wenjing Pan; Jiannan Lin; Jie Su; Jingfeng Fan (Regional Studies in Marine Science, 2026)

Development of a hydrazinolysis method for the determination of vinclozolin in foods by SPE and GC–MS/MS - Hongxia Tang; Yubo Li; Qinyi Sheng; Rui Yu; Dongwei Wang; Lin Ma; Guangyue Wen; Maofeng Dong; Xianbin Li; Li Zhao (Food Chemistry, 2026)

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

Adenosine A1 receptor in the medial parabrachial nucleus modulates sleep-wake regulation and homeostatic processes - Minrui Zhao; Jin Huang; Yue Zhang; Ronghua Liao; Lin Zhang; Hongxia Li; Juan Wang (Sleep and Biological Rhythms, 2026)

An explainable machine learning model for accurate estimation of residual phthalate esters in Chinese agricultural soils - Weiwei Wang; Laigang Hu; Jialu Xu; Hongxia Zhu; Shuping Xing; Zhen Song; Yuchen Shen; Daohui Lin; Zhou Shi; Kun Yang (Journal of Hazardous Materials, 2026)

Construction of SnO2/Bi2O2CO3 Z-type heterojunction for photocatalytic degradation of humic acid under sunlight - Muxi Zhang; Chenchen Liao; Bin Dong; Wenjie Lin; Yu Chen; Penghui Yao; Xiaojie Sun; Hongxia Zhang (Environmental Research, 2026)

Synergistic piezo-triboelectricity in ultra-thick PVDF-PAN nanofiber membranes for high-power energy harvesting and intensive force sensing - Peng Jiang; Lu Peng; Hongxia Wang; Wenyu Wang; Xin Jin; Tong Lin (Chemical Engineering Journal, 2026)

Research on the application of nanopore sequencing technology in investigating microbial data deviation - Xiaoling Zheng; Hongxia Yang; Wanzi Gong; Shiyu Wang; Yinhuan Wang; Deyin Deng; Tingzhang Wang; Hong Li; Chenshui Lin (Antonie van Leeuwenhoek, 2026)

Discovery and engineering of a new BvCas12a nuclease for mammalian genome editing and nucleic acid detection - Xuechun Shen; Lei Huang; Dan Wang; Chen Qi; Baitao Li; Chuan Liu; Ke Chen; Yuanqiang Zou; Liang Xiao; Yuan Jiang; Qiupeng Lin; Hongxia Lan; et al. (Science China Life Sciences, 2026)

Enhanced SO2 resistance of the Pd/Silicate-1 catalyst by rare earth oxide modification in methane combustion - Jinxiong Tao; Hongxia Lin; Yuxi Liu; Jiguang Deng; Lin Jing; Zhiwei Wang; Lu Wei; Zhen Wei; Zhiquan Hou; Zexu Zhang; Hongxing Dai (Journal of Environmental Sciences, 2026)

Moisture-resistant Al-based MOF with helical SBUs for efficient CO2 adsorption, separation and desorption - Laigang Hu; Weiwei Wang; Ling Jiang; Jinru Hu; Hongxia Zhu; Mengxue Zhang; Jian Wu; Daohui Lin; Kun Yang (Chemical Engineering Journal, 2026)

Advancing Non‐Contact Fish Phenotyping via Optical Sensing: Toward Precision Aquaculture - Kai Lin; Shiyu Zhang; Wei Wang; Tian Dong; Wen Ding; Chenfan Geng; Yihang Lu; Hongxia Hu (Reviews in Aquaculture, 2026)
Non‐contact fish phenotyping has become an essential strategy for precision aquaculture, enabling accurate, high‐throughput, and non‐invasive trait measurement. In this review, a digital phenotyping framework is summarized, including application‐driven trait definition, multimodal data acquisition (2D, 2.5D, and 3D imaging), and automated phenotypic analysis based on computer vision and deep learning. According to current research paradigms, optical phenotyping applications are systematically categorized into three major domains: morphological, behavioral, and appearance‐based phenotyping. Multimodal optical sensing systems now support high‐throughput morphological, behavioral, and appearance‐based phenotyping, enabling applications ranging from biomass estimation and intelligent feeding control to selective breeding, product quality evaluation, species identification, and disease diagnosis. Despite rapid methodological progress, most existing studies remain confined to laboratory or semi‐controlled environments, and large‐scale implementation in commercial production systems is still limited. Key challenges persist in underwater image degradation, posture‐induced measurement uncertainty, data heterogeneity, model generalizability, computational constraints, and the integration of phenotypic and genomic data for precision breeding. Finally, future development pathways are discussed, including efficient and flexible data acquisition platforms, lightweight and real‐time processing, transfer and few‐shot learning, multimodal data fusion, novel phenotype quantification, and standardized open datasets. Based on a comprehensive analysis of over 100 studies, this review maps the current technological landscape and proposes pathways toward scalable, intelligent phenotyping systems that can improve fish welfare, enhance breeding efficiency, and promote sustainable aquaculture management.

A novel method for controllable and interpretable load scenario generation based on LPR-Net and SRGAN - Hongxia Guo; Yuan Li; Lin Li; Jianxue Wang; Qian Ma (Energy and Buildings, 2025)

Corrigendum to “Evaluation of bacteriostatic and antioxidant screening of secondary metabolites of endophytic fungi in Lanzhou lily” [Bioresour. Technol. Rep. 32 (2025) 102380] - Xinlan Wang; Bolu Sun; Ying Lv; Miao Zhou; Xuanxiu Da; Jiali Kang; Haiying He; Chenyu Qin; Quhuan Ma; Hongxia Shi; Lin Yang; Xiaofeng Shi (Bioresource Technology Reports, 2025)

Evaluation of bacteriostatic and antioxidant screening of secondary metabolites of endophytic fungi in Lanzhou lily - Xinlan Wang; Bolu Sun; Ying Lv; Miao Zhou; Xuanxiu Da; Jiali Kang; Haiying He; Chenyu Qin; Quhuan Ma; Hongxia Shi; Lin Yang; Xiaofeng Shi (Bioresource Technology Reports, 2025)

Polyvinylidene fluoride/polysulfone nanofiber membranes with dual high-efficiency and self-regenerating filtration for solid-oil aerosols - Le Xu; Peng Jiang; Lu Peng; Chaochen Cai; Yongji Lu; Zhenyu Zhu; Hongxia Wang; Xin Wei; Tong Lin (Chemical Engineering Journal, 2025)

Efficient removal of antibiotics and synthetic dyes using VTMS-functionalized N/S-GQDs-PVA/cellulose composite aerogels - Muhammad Yousif; Meiling Zhang; Bilqees Hussain; Xupin Zhuang; Zhangang Wang; Hongxia Wang; Tong Lin (Chemical Engineering Journal, 2025)

Association of urinary phthalate metabolites and polycystic ovary syndrome in women undergoing in vitro fertilization - Wenjie Zhou; Shuifang Lei; Hong Lv; Yangqian Jiang; Tianyu Sun; Yanjie Zhang; Hongxia Ma; Jie Wu; Yuan Lin (Reproductive Toxicology, 2025)

PRDM14 promoted NSCLC cell proliferation, migration and invasion via modulating H3K27me3-mediated PEBP1/Raf-1/MEK/ERK MAPK signaling - He Shi; Yunfei Jiang; Haijun Mu; Guohua Liu; Xinyue Cheng; Weili Kong; Xingqi Zhou; Xiaoqiang Wen; Xiao Wang; Yiyu Lin; Linyu Pan; Haiying Dong; et al. (Genes & Genomics, 2025)

Catalytic oxidation of volatile organic compounds over supported noble metal and single atom catalysts: A review - Honghong Zhang; Zhiwei Wang; Hongxia Lin; Yuxi Liu; Hongxing Dai; Jiguang Deng (Journal of Environmental Sciences, 2025)

Screening of biocontrol agents against lily bulb rot caused by F. oxysporum and research on their fermentation process - Bolu Sun; Xinlan Wang; Ying Lv; Xuanxiu Da; Miao Zhou; Jiali Kang; Haiying He; Chenyu Qin; Xiangdong Wang; Lin Yang; Quhuan Ma; Hongxia Shi; et al. (Bioresource Technology Reports, 2025)

Assessment of spatial and temporal variability in fecal contamination patterns within urbanized bay shellfish growing area utilizing community-based microbial source tracking approaches - Jiannan Lin; Hongxia Ming; Dongwei Li; Jiajie Li; Zhongzhi Chen; Ziqi Chen; Tingting Shi; Jie Su; Jingfeng Fan (Environmental Monitoring and Assessment, 2025)

Construction of P450 scaffold biocatalysts for the biodegradation of five chloroanilines - Ridong Yang; Osami Shoji; Yingwu Lin; Fang Wang; Hongxia Che; Jiakun Xu (Journal of Hazardous Materials, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Model-informed Drug Development (MIDD) Approach to Support Biopharmaceutical Development of Iberdomide - Caroline Sychterz; Ping Chen; Ajay Saxena; Hongxia Lin; Lu Chen; Yan Li; Lu Gaohua; Yiming Cheng (The AAPS Journal, 2025)
Iberdomide is a BCS III CELMoD™ agent currently under development for treatment of multiple myeloma. Five formulations were used during clinical development, starting with active ingredient in gelatin capsule (AIC), followed by subsequent formulations in gelatin (F1), HPMC capsules (F2 and F3), and finally the intended commercial form (ICF). A food effect study with the Phase I AIC formulation showed no food effect and two relative bioavailability studies bridging from AIC to formulation F1 and F2 showed similar systemic exposure. Modeling and simulation, based on in vitro dissolution, was used to bridge gaps in clinical data to demonstrate lack of a food effect across all formulations including ICF. First, a previously developed population pharmacokinetic (PK) model showed that formulation was not a covariate on iberdomide PK. Then a physiologically-based pharmacokinetic model (PBPK) informed by in vitro biorelevant dissolution was used to mechanistically describe iberdomide absorption. While minor differences between formulations were noted in their in vitro dissolution, PBPK modeling showed lack of a food effect across all five formulations. Sensitivity analysis using the PBPK model demonstrated that iberdomide permeability and total amount of drug released from formulation are the most sensitive parameters in defining the systemic exposure of iberdomide, in agreement with iberdomide’s BCS III classification where drug release from drug product, and not solubility, is the rate-limiting step of dissolution. Based on the totality of evidence, which included clinical and in vitro data supplemented by modeling and simulation, no food effect is expected with the ICF. Graphical Abstract

Selective degradation of KOH activated biochar adsorbed 4-chlorophenol with fulvic acid by peroxydisulfate - Min Hu; Laigang Hu; Xiaozeng Miao; Limin Duan; Ling Jiang; Hongxia Zhu; Wenhao Wu; Daohui Lin; Kun Yang (Journal of Environmental Chemical Engineering, 2025)

PLATZ transcription factors and their emerging roles in plant responses to environmental stresses - Hongxia Zhang; Lu Liu; Zhenzhen Li; Shuo Wang; Li Huang; Sue Lin (Plant Science, 2025)

Antioxidant response fail to rescue growth of Hermetia illucens L. larvae induced by copper accumulated during long-term exposure - Huijie Zhang; Hongxia Sun; Lin Liu; Ye Liao; Yanxin Lu; Qiang Xia (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Carbon dots-based stimuli-responsive hydrogel for in-situ detection of thiram on fruits and vegetables - Hongxia Li; Yanan Hu; Zhen Lin; Xu Yan; Chunyan Sun; Dong Yao (Food Chemistry, 2024)

Inter‐algal associations and nutrients linked by Scenedesmus and Desmodesmus structure eukaryotic algal communities - Juan Lin; Hongxia Wang; Jianfeng Chen; Yun Li (Molecular Ecology, 2024)
Eutrophication reduces the variability of the community composition of plankton. However, the mechanisms underlying the diversity and restructuring of eukaryotic algal communities remain unknown. This study analysed the diversity and compositional patterns of algal communities in shallow eutrophic lakes. It investigated how these communities were modified by key genera through mediating inter‐algal associations under the influence of abiotic factors. Inter‐algal associations explained more variance in algal communities than environmental variables, and variation in composition and diversity was primarily derived from Scenedesmus , Desmodesmus and Cryptomonas , rather than nutrients. Scenedesmus and Desmodesmus were positively correlated with the genera of Chlorophyta and formed the hub of the algal association network. When the relative abundance of Scenedesmus and Desmodesmus increased from 0.41% to 13.74%, communities enriched in biomarkers of Bacillariophyta, Chrysophyceae and Cryptophyta transitioned to communities enriched in biomarkers of Chlorophyta. Moreover, negative associations between the Chlorophyta hub genera and other non‐Chlorophyta genera increased. High concentrations of total phosphorus altered the composition of algal communities by increasing the abundance of Scenedesmus and Desmodesmus , which in turn had cascading effects through inter‐algal associations. Additionally, algal communities with higher abundances of Scenedesmus and Desmodesmus were more susceptible to the effects of total phosphorus. Our study suggested that inter‐algal associations, centred on Scenedesmus and Desmodesmus , had a greater influence on algal diversity and community structure than other factors. Nutrient levels were not a direct driver of algal diversity and community structure adjustments, but acted indirectly by enhancing the influence of Scenedesmus and Desmodesmus .

Green synthesis of a superhydrophobic porous organic polymer for the removal of volatile organic compounds at high humidity - Hongxia Zhu; Li Gong; Ling Jiang; Xianyu Liu; Laigang Hu; Wenhao Wu; Daohui Lin; Kun Yang (Science of The Total Environment, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Glutathione‑iron hybrid nanozyme-based colorimetric sensor for specific and stable detection of thiram pesticide on fruit juices - Xu Yan; Ruiqi Zou; Qiqi Lin; Yuan Ma; Aixin Li; Xun Sun; Geyu Lu; Hongxia Li (Food Chemistry, 2024)

CD146, a therapeutic target involved in cell plasticity - Zhenzhen Wu; Yuzhe Zang; Chuyi Li; Zhiheng He; Jingyu Liu; Zhaoqi Du; Xinran Ma; Lin Jing; Hongxia Duan; Jing Feng; Xiyun Yan (Science China Life Sciences, 2024)

Promoting the denitrification process by heavy metals in Liaohe Estuary sediment - Ming Hongxia; Zan Shuaijun; Liu Jiwen; Su Jie; Ren Kaijia; Lin Jiannan; Chen Quanrui; Shi Yinyin; Shi Tingting; Fan Jingfeng (Marine Pollution Bulletin, 2024)

Phthalate and DINCH exposure and ovarian reserve markers among women seeking infertility care - Yangqian Jiang; Yiqun Xu; Shuxin Xiao; Xianxian Zhu; Hong Lv; Lu Zang; Shuifang Lei; Xin Xu; Bo Xu; Xiumei Han; Jin Zhu; Jiangbo Du; et al. (Science of The Total Environment, 2024)

Aquaculture PPP development in China-case study from Hani Terrace - Yuan Yuan; Gangchun Xu; Pao Xu; Hongxia Li; Lin Zhang; Zhijuan Nie; Pierre Murekezi; Xiao Liang; Zhengyong Yang; Xinhua Yuan (Marine Policy, 2024)

Unravelling the synergy of platinum-oxygen vacancy in CoOx for modulating hydrogenation performance - Hao Xu; Hongxia Zhang; Lin Cui; Xinshuo Zhao; Jiao Xiao; Jian Zhang; Yong Qin; Jiankang Zhang (Chemical Engineering Journal, 2024)

The heterogeneous impact of green public procurement on corporate green innovation - Mingting Kou; Lin Zhang; Hongxia Wang; Yufei Wang; Zitong Shan (Resources, Conservation and Recycling, 2024)

Hydrological characteristics of the Bering Sea in the summer of 2019 - Hongxia Chen; Lina Lin; Long Fan; Bin Kong; Yan He; Zexun Wei; Na Liu; Yida Xu (Marine Environmental Research, 2024)

PCAP-1a, an exopolysaccharide from Pectobacterium actinidiae, exerts the dual role of immunogenicity and virulence in plants - Zhixiang Yuan; Tingmi Yang; Qingping Xiong; Yuqi Shi; Xixi Han; Yuqing Lin; Njoroge Hellen Wambui; Zhuang Liu; Yunpeng Wang; Hongxia Liu (Carbohydrate Polymers, 2024)

Observation of Arctic surface currents using data from a surface drifting buoy - Hongxia Chen; Lina Lin; Long Fan; Wangxiao Yang; Yinke Dou; Bingrui Li; Yan He; Bin Kong; Guangyu Zuo; Na Liu (Acta Oceanologica Sinica, 2024)

Organic anion transporting polypeptide 3a1 is a novel influx pump for Perfluorooctane sulfonate in Sertoli cells and contributes to its reproductive toxicity - Ting Li; Lianlian Jiang; Shaokai Zheng; Chong Qiu; Nannan Zhao; Xiaojun Lin; Hang Ren; Jiyan Huang; Hongxia Wang; Lianglin Qiu (Chemosphere, 2023)

Encapsulation of lutein in gelatin type A/B-chitosan systems via tunable chains and bonds from tweens: Thermal stability, rheologic property and food 2D/3D printability - Hongxia Wang; Xianyou Lin; Juncheng Zhu; Yuxin Yang; Shihao Qiao; Bo Jiao; Liang Ma; Yuhao Zhang (Food Research International, 2023)

Association between PM2.5 exposure and the outcomes of ART treatment: A prospective birth cohort study - Yifan Wang; Yun Qiu; Bo Huang; Jiangbo Du; Liya Liu; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; et al. (Science of The Total Environment, 2023)

Association between prenatal exposure to trace elements mixture and visual acuity in infants: A prospective birth cohort study - Zijin Wang; Yuanyan Dou; Wenhui Guo; Yuan Lin; Yangqian Jiang; Tao Jiang; Rui Qin; Hong Lv; Qun Lu; Guangfu Jin; Hongxia Ma; Zhibin Hu; et al. (Chemosphere, 2023)

Gut Microbiota in Children with Hand Foot and Mouth Disease on 16S rRNA Gene Sequencing - Yan Zhuang; Yiyan Lin; Hongxia Sun; Zaiting Zhang; Tao Wang; Rongjun Fan; Lu Han (Current Microbiology, 2023)

Prediction of zebrafish embryonic developmental toxicity by integrating omics with adverse outcome pathway - Xiao Gou; Cong Ma; Huimin Ji; Lu Yan; Pingping Wang; Zhihao Wang; Yishan Lin; Nivedita Chatterjee; Hongxia Yu; Xiaowei Zhang (Journal of Hazardous Materials, 2023)

Association between long-term exposure to air pollution and the risk of incident laryngeal cancer: a longitudinal UK Biobank-based study - Jiada Wang; Chen Lin; Yidian Chu; Hongxia Deng; Zhisen Shen (Environmental Science and Pollution Research, 2023)
We assessed the association between long-term joint exposure to ambient air pollutants and the risk of laryngeal cancer and whether this risk was modified by genetic susceptibility. We used a multivariable Cox proportional hazards regression model to analyze data from UK Biobank to determine the relationship between long-term exposure to air pollutants–nitric oxide (NO), nitrogen dioxide (NO 2 ), and 2.5- µ m and 10- µ m particulate matter (PM 2.5 and PM 10 ) and the risk of laryngeal cancer. In multivariable-adjusted models, in model 3 and compared with the participants with lower quintile scores for air pollution, the participants with the highest quintile scores for air pollution had a higher laryngeal cancer risk. The observed association was more pronounced among the participants who were female, were smokers, had a systolic blood pressure equal to or greater than 120 mmHg, and had diabetes. Compared with the participants with a low GRS and the lowest quintile score for air pollution exposure, those with an intermediate GRS and the highest quintile score for air pollution exposure had a higher risk of laryngeal cancer. Long-term exposure to NO 2 , NO, or PM 2.5 , individually or jointly, was associated with a risk of incident laryngeal cancer, especially in the participants with an intermediate GRS.

A novel monoclonal antibody efficiently blocks the infection of duck adenovirus 3 by targeting Fiber-2 - Yun Lin; Wenyuan Zhang; Jing Xie; Quan Xie; Tuofan Li; Zhimin Wan; Hongxia Shao; Aijian Qin; Jianqiang Ye (Veterinary Microbiology, 2023)

Graphitic carbon nitride-based photocatalysts in the applications of environmental catalysis - Hongxia Lin; Jinmo Wu; Fan Zhou; Xiaolong Zhao; Pengfei Lu; Guanghui Sun; Yuhan Song; Yayun Li; Xiaoyong Liu; Hongxing Dai (Journal of Environmental Sciences, 2023)

Melanin from Sepia pharaonis ink alleviates mucosal damage and reduces inflammation to prevent alcohol-induced gastric ulcers - Lin Liu; Kuan Lu; Jingwen Xie; Hongxia Che; Hongyan Li; Xie Wancui (Food Bioscience, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Identification of high-concern organic pollutants in tap waters from the Yangtze River in China based on combined screening strategies - Liben Chou; Chengzhuo Zhou; Wenrui Luo; Jing Guo; Yanhong Shen; Die Lin; Chang Wang; Hongxia Yu; Xiaowei Zhang; Si Wei; Wei Shi (Science of The Total Environment, 2023)

The Flavor and Antioxidant Activity Change Pattern of Shrimp Head Paste During Fermentation - Jing Yu; Kuan Lu; Jinyuan Sun; Wancui Xie; Lin Song; Hongxia Che (Journal of Ocean University of China, 2022)

A Comparative Study About the Neuroprotective Effects of EPA-Enriched Phosphoethanolamine Plasmalogen and Phosphatidylethanolamine Against Oxidative Damage in Primary Hippocampal Neurons - Yunfang Zhu; Tiantian Zhang; Lin Ding; Haohao Shi; Changhu Xue; Wancui Xie; Hongxia Che; Yuming Wang (Journal of Ocean University of China, 2021)

Study on dynamic mechanical properties of phosphate rock through experimental tests and mesoscale simulation - Xiqi Liu; Gang Wang; Tingting Liu; Manqing Lin; Hongxia Lei; Abhay Kumar Mandal (Arabian Journal of Geosciences, 2020)

Clinical characteristics of 24 asymptomatic infections with COVID-19 screened among close contacts in Nanjing, China - Zhiliang Hu; Ci Song; Chuanjun Xu; Guangfu Jin; Yaling Chen; Xin Xu; Hongxia Ma; Wei Chen; Yuan Lin; Yishan Zheng; Jianming Wang; Zhibin Hu; et al. (Science China Life Sciences, 2020)

Methamphetamine-Induced Cognitive Deficits and Psychiatric Symptoms Are Associated with Serum Markers of Liver Damage - Tingting Zhao; Changping Zhai; Hongmei Song; Yanhai Wu; Chuanhui Ge; Yonglin Zhang; Hongxia Xu; Zhengsuo Chi; Hui Chu; Wei Shi; Xiaodong Cheng; Xin Li; et al. (Neurotoxicity Research, 2020)

Complete genome sequence of an alternavirus from the phytopathogenic fungus Fusarium incarnatum - Xiaoting Zhang; Yuan Xie; Fang Zhang; Hangjun Sun; Yingying Zhai; Songbai Zhang; Hongxia Yuan; Lin Zhou; Fei Gao; Honglian Li (Archives of Virology, 2019)

The complete genomic sequence of a novel megabirnavirus from Fusarium pseudograminearum, the causal agent of wheat crown rot - Xiaoting Zhang; Fei Gao; Fang Zhang; Yuan Xie; Lin Zhou; Hongxia Yuan; Songbai Zhang; Honglian Li (Archives of Virology, 2018)

A cis-eQTL genetic variant of the cancer–testis gene CCDC116 is associated with risk of multiple cancers - Na Qin; Cheng Wang; Qun Lu; Tongtong Huang; Meng Zhu; Lihua Wang; Fei Yu; Mingtao Huang; Yue Jiang; Juncheng Dai; Hongxia Ma; Guangfu Jin; et al. (Human Genetics, 2017)

Novel avian leukosis viruses from domestic chicken breeds in mainland China - Hongxia Shao; Lin Wang; Jianjun Sang; Tuofan Li; Yuelong Liu; Zhimin Wan; Kun Qian; Aijian Qin; Jianqiang Ye (Archives of Virology, 2017)

Association of MMP-9 C-1562T polymorphism with risk of Henoch-Schönlein purpura nephritis in children of southeast China - Jinwen Xu; Liping Zhao; Hongxia Zhou; Tingting Ge; Lin Zhang (Genes & Genomics, 2017)

The distribution and inter-annual variation of water masses on the Bering Sea shelf in summer - Na Liu; Lina Lin; Yingjie Wang; Hongxia Chen; Yan He (Acta Oceanologica Sinica, 2016)

The characteristics of warm water inflowing and its temporal and spatial variation on the Prydz Bay continental shelf, Antarctic - Lina Lin; Hongxia Chen; Na Liu (Acta Oceanologica Sinica, 2016)

Arctic autumn sea ice decline and Asian winter temperature anomaly - Na Liu; Lina Lin; Yingjie Wang; Bin Kong; Zhanhai Zhang; Hongxia Chen (Acta Oceanologica Sinica, 2016)

Association between Arctic autumn sea ice concentration and early winter precipitation in China - Na Liu; Lina Lin; Bin Kong; Yingjie Wang; Zhanhai Zhang; Hongxia Chen (Acta Oceanologica Sinica, 2016)

Effects of 3,5-Diiodotyrosine and Potassium Iodide on Thyroid Function and Oxidative Stress in Iodine-Excess Wistar Rats - Dan Liu; Xinying Lin; Fugui Yu; Man Zhang; Hongxia Chen; Wei Bao; Xia Wang (Biological Trace Element Research, 2015)

Pharmacokinetics and pharmacodynamics of 3,3′-diindolylmethane (DIM) in regulating gene expression of phase II drug metabolizing enzymes - Tien-Yuan Wu; Ying Huang; Chengyue Zhang; Zheng-Yuan Su; Sarandeep Boyanapalli; Tin Oo Khor; Hu Wang; Hongxia Lin; Murugesan Gounder; Leonid Kagan; Ioannis P. Androulakis; Ah-Ng Tony Kong (Journal of Pharmacokinetics and Pharmacodynamics, 2015)

Observed features of temperature, salinity and current in central Chukchi Sea during the summer of 2012 - Yan He; Na Liu; Hongxia Chen; Fei Teng; Lina Lin; Huiwu Wang (Acta Oceanologica Sinica, 2015)

Genetic variants at 4q21, 4q23 and 12q24 are associated with esophageal squamous cell carcinoma risk in a Chinese population - Yong Gao; Yisha He; Jing Xu; Lin Xu; Jiangbo Du; Chen Zhu; Haiyong Gu; Hongxia Ma; Zhibin Hu; Guangfu Jin; Xiaofei Chen; Hongbing Shen (Human Genetics, 2013)

Application of biopharmaceutics classification system (BCS) in drug transport studies across human respiratory epithelial cell monolayers - Hyun-Jong Cho; Prabagar Balakrishnan; Hongxia Lin; Min-Koo Choi; Dae-Duk Kim (Journal of Pharmaceutical Investigation, 2012)

Novel human BTB/POZ domain-containing zinc finger protein ZBTB1 inhibits transcriptional activities of CRE - Qingmei Liu; Feng Yao; Minghua Wang; Bin Zhou; Hongxia Cheng; Weiping Wang; Li Jin; Qiang Lin; Jiu-Cun Wang (Molecular and Cellular Biochemistry, 2011)

Western Indian Ocean SST signal and anomalous Antarctic sea-ice concentration variation - Na Liu; Zhanhai Zhang; Hongxia Chen; Lina Lin (Acta Oceanologica Sinica, 2011)